Fast Transfer Hydrogenation(TH) in Aerobic Condition and Oxidation of Alcohols with N‐Methylmorpholine‐N‐oxide Catalyzed by Ru(II) Ligated with Chalcogenated Pyridines and PPh3. Issue 31 (18th August 2020) - Kumar, Rajan; Singh, Ved Vati; Jain, Nidhi; Singh, Ajai K.
Abstract: The transfer hydrogenation (TH) of aldehydes / ketones (at mmol level), using propan‐2‐ol as a H‐source is complete within 15 min when catalyzed by 0.1 mol% of [Ru(L )(PPh3 )Cl2 ]] (1–4 ; L =L1–L4 ; L1 /L2 =( E )‐2‐(phenylthio/seleno)‐ N ‐(pyridin‐2‐ylmethyene)ethan‐amine, L3/L4 =2‐(phenylthio/seleno)‐ N ‐(pyridin‐2‐ylmethyl)ethan‐ amine). The 1–4 were prepared by treating [Ru(PPh3 )3 Cl2 ] with L1–L4 respectively.The L1–L4 and 1–4 were characterized by 1 H, 13 C 1 H and 77 Se 1 H NMR spectra. Single crystal structures of 1–4 determined by X‐ray diffraction revealed distorted octahedral geometry of Ru in each complex and bond lengths (Å) as: Ru−S, 2.3441(1) and 2.335(3) and Ru−Se, 2.4497(2) and 2.4518(4). Each of 1–4 ( 0.1 mol%) is almost equally efficient as catalyst for TH and oxidation of alcohols with N ‐methylmorpholine‐ N ‐oxide (NMO). The optimum amount of oxidant NMO was found 3 mmol for 1 mmol of alcohol. In ambient conditions both the catalytic reactions by the four complexes appear to be homogeneous. The scope of substrates for both the reactions is reported. Abstract : TH of aldehydes/ketones(mmol) catalyzed with [Ru(chalcogenated pyridine)(PPh3 )Cl2 ]](1‐4), takes 15 min and catalytic (by1‐4) selective oxidation of alcohols with NMO requires5 h. Catalytic efficiency of 1–4 does not differ significantly. TH of aliphatic as well as aromatic aldehydes/ketones is feasible Tentative mechanism of the catalytic reactions are proposed. Ru(IV)=O species are involved in oxidation and those responsibe for TH probably have Ru−H bond